Selection and Molecular Characterization of Soybeans with High Oleic Acid from Plant Germplasm of Genebank - Lee, Kyung Jun; Lee, Jung-Ro; Shin, Myoung-Jae; Cho, Gyu-Taek; Ma, Kyung-Ho; Chung, Jong-Wook; Lee, Gi-An (Journal of Crop Science and Biotechnology, 2019)
Altering soybean fatty acid profiles to improve soybean oil quality has long been time goal of soybean researchers. Soybean oil with elevated oleic acid is desirable because this monounsaturated fatty acid improves the nutrition and oxidative stability of soybean oil compared with other oils. The objective of this study was to select soybean accessions with high oleic acid from genetic germplasm and to identify novel sources of the genetic variation for high oleic acid in soybeans. Ten candidate soybean accessions with high oleic acid were identified in the Genebank Management System at the National Agro-Biodiversity Center, NAS, Rural Development Administration, Republic of Korea. Three accessions with high oleic acid were selected: IT104821, IT143166, and IT162509. Comparisons of the FAD2-1A and FAD2-1B sequences in the three soybeans with those in a gene with normal oleic acid (IT162718) and with the NCBI database showed that the differences in these genes affected a highly conserved group of three histidine residues that are necessary for enzymatic activity. FAD2-1A in IT162509 contained a single nucleotide polymorphism (A944G) that changed histidine (H315, the third histidine motif) to arginine. FAD2-1B in IT104821 and IT143166 were the T insertion, creating a stop codon that prematurely terminated translation. These results suggest that gene analysis based on DNA sequencing could be useful for identifying FAD2-1 in soybean germplasm. Additionally, the soybean accessions selected in this study could be used to develop soybean cultivars with high oleic acid.